Telling People to Change Their Behaviour Through Implications: An Implicature Analysis on Covid-19 Public Service Announcements in Indonesia - Marbun, Susan; Silalahi, Dumaris E.; Herman, Herman (Universitas Lancang Kuning, 2021)
Public service announcements (PSAs) are the official way for governments to inform, educate and change public behaviour in order to reduce public health issues, such as Covid-19. This study aims to analyse the types of implicatures in the Covid-19 PSAs published by the Ministry of Health Republic of Indonesia in their Instagram account, @kemenkes_ri, in order to fill the research gap on implicature studies in a public health and political contexts. This qualitative descriptive research analysed a data of eleven Covid-19 PSAs which were published from March 2020 to January 2021 according to Grice’s implicature theory. The researchers discovered that PSAs employed conversational implicatures more frequently than conventional implicatures (18%) to deliver their messages, with generalised conversational implicature being more prevalent (64%) than particularised conversational implicature (18%). Conventional implicature was used only in earlier posts when Covid-19 has not been a common knowledge among the public, and once people are already used to the “new normal”, alter PSAs used conversational implicature because the public already have the context of Covid-19. Results of this study illuminated the differences between each type of implicatures and also contributed to the lack of studies of PSAs’ implied meanings, the dearth of implicature studies in a non-classroom context.